A mitigation simulation method for urban NOx emissions based on input-output analysis. (10th March 2020) - Xu, Xinli; Huang, Guohe; Liu, Lirong; Li, Jizhe; Zhai, Mengyu
Abstract: With the frequent occurrence of global warming, acid rain, and photochemical smog, nitrogen oxide (NOx) pollution has become an increasingly serious global problem. It is essential to establish efficient approaches for seeking reasonable and practical mitigation pathways. In this paper, a NOx mitigation simulation (NMS) model is developed to facilitate the development of mitigation policies. Through constructing the NOx metabolic network, all sectors are classified according to their interactions. With production-side and consumption-side mitigation strategies adopted for different categories respectively, the changes of sectoral and system-wide indirect emissions are accounted for under the framework of urban metabolism. The results of the case study for Guangdong Province, China, illustrate that the mitigation strategies aimed at the specific sectors of the economy might not be as practical as expected. Both the type of mitigation strategies and the sector category it interferes with have a decisive influence on reduction performance. In Guangdong Province, regulating electricity, heat power generation and smelting, pressing of metals can achieve substantial reduction performance through production-based ways, and supervising the sectors with weak control and strong dependence (e.g., Construction and Other social services) is the most effective measure on the consumption side. The comprehensive mitigation strategies made from production and consumption perspectives are capable of acquiring the most efficient reduction performance. Considering cities as an ecosystem, the mitigation simulation framework established in this study has the potential to assess and formulate reduction policies of NOx emissions. Highlights: An urban NOx mitigation simulation model (NMS) is developed. All sectors are classified according to their ecological interactions. Different mitigation strategies are adopted for each sector category respectively. The effectiveness of various strategies for emission reductions is evaluated. The data analysis is conducted by MATLAB.